Comprehensive Student Management at SMP IT Daarul Hidayah: Integrating Potential Screening, the Qirā’atul Kutub Tahfidz Program, and Administrative Documentation. - Rini Qonitah; Dartim (Institut Agama Islam An-Nawawi Purworejo, 2026)
Student management is a strategic issue in improving school quality because it determines the regularity of student services from admission to graduation. In the context of integrated Islamic schools, the urgency of student management is even higher because schools are not only required to produce academic achievements, but also strengthen religious character development through flagship programs. This study aims to describe and analyze the implementation of end-to-end student management based on SOPs at SMP IT Daarul Hidayah, specifically the integration of potential screening, tahfidz-qirā’atul kutub programs, and administrative documentation as a service quality control mechanism. The study uses a descriptive, qualitative approach with a case-study strategy; data were collected through observation, in-depth interviews, and documentation (student SOPs, master books, clapper books, ledger books, and BK records). Data analysis was carried out interactively through data reduction, data presentation, and concluding/verification with triangulation of sources and methods to maintain credibility. The findings indicate that student management is implemented through structured stages of planning, diagnostic-inclusive PPDB, orientation and screening, role organization (Waka Kesiswaan, Homeroom Counselor, BK), character development through class routines and flagship programs, extracurricular/OSIS management as a discipline and leadership instrument, and comprehensive, systematically documented academic-attitude assessments. This system has an impact on increasing the regularity of coaching, trackability of student development data, and strengthening the school's identity through